ANALISIS KARAKTERISTIK IBU, PERILAKU AKSES AIR MINUM DAN SANITASI LAYAK TERHADAP KEJADIAN STUNTING BALITA DI KABUPATEN KEROOM - Nawang Wulan; Renold Markus Mofu; Amiruddin Amiruddin (NHM PRESS, 2022)
Stunting is a condition of failure to thrive in children under five as a result of chronic malnutrition so that children are too short for their age. This study uses a quantitative research approach with a cross sectional design. The population is all toddlers in Arso Village, totaling 99. The sampling technique is total sampling. So the number of samples is 99. Data analysis with logistic regression test. There is no relationship between characteristics of maternal age (p value 0.066), characteristics of mother's education (P value 0.392), characteristics of mother's work (P value 0.813), with the incidence of stunting in children under five in Keroom Regency in 2021. There is no relationship between knowledge about safe drinking water (p value 0.362), attitudes about drinking water (p value; 0.745), access to drinking water (P Value 0.221), knowledge of proper sanitation (p Value: 0.396), attitudes about proper sanitation (p Value: 0.076), access to proper sanitation with stunting incidence in children under five in Keroom Regency in 2021 (P value: 0.196).